Camouflage Personae: A Case Study of Bapsi Sidhwa’s ‘The Pakistani Bride’ - Nawaz, Muhammad (International Journal of English Literature and Social Sciences (IJELS), 2019)
The study is conducted to investigate Bapsi Sidhwa’snovel The Pakistani Bride in order to explore that howmany kinds ofdefense mechanisms are used by the characters to evaluate the consequences of these defense mechanisms. Sigmund Freud’s defense mechanism theory is used to sort out the answers of these questions. The research discloses that both novels in characters use defense mechanism and they show moral anxiety due to family background and society. The research finds out that Ziatoon uses defense mechanism that was connected to self-amendment. Ziatoon has faced many problems in life by virtue of fate and society but she never gave up andcarried on her journey against the typical norms of the society. She presents certain examples howshefaced conflicts and frustration from the society. Rationalization assists her to defeat anxiety and guidesher to experience new things and new people. Like Ziatoon, people may use defense mechanisms in order to do something.